PENTINGNYA PERUSAHAAN DALAM MENERAPKAN PRINSIP GOOD CORPORATE GOVERNANCE - Pertiwi Ananda Putri, Devi; Trisnaningsih, Sri (Penerbit Lafadz Jaya, 2023)
Corruption, Collusion and Nepotism practices, especially corrupt practices, are still a problem that occurs in Indonesia from the past until now. One of the factors that causes corruption is the implementation of Good Corporate Governance which is still weak and inconsistent. This article aims to analyze the importance of implementing GCG in companies using the literature study method from several articles that discuss the topic to be discussed. The results of this research are that there are five principles of Good Corporate Governance, namely Transparency, Accountability, Responsibility, Independence and Fairness. Implementing GCG well and implementing it consistently will have a positive impact on the company itself, such as increasing company performance, improving the welfare of company employees and preventing fraudulent acts that are detrimental to the company and other parties. On the other hand, poor and weak implementation of GCG which is not carried out consistently creates loopholes which cause fraud to occur.